Association between dopamine beta‐hydroxylase polymorphism and attention function in suicide attempters with chronic schizophrenia. (8th September 2020) - Hui, Li; Hu, Wei Ming; Zhu, Zhen Hua; Gao, Song Tian; Han, Mei; Fan, Yu; Tian, Qing; Yin, Xu Yuan; Yuan, Ying; Jiang, Cai Xia; Yin, Guang Zhong; Jia, Qiu Fang; et al.
Abstract: Background: Patients with schizophrenia are at a higher risk for suicide compared with the general population. Dopamine beta‐hydroxylase ( DβH ) plays a key role in the conversion of dopamine to norepinephrine, which is related to suicidal behavior and cognitive regulation. Objective: To examine whether there is the effect of DβH 5′ ‐ insertion/deletion (Ins/Del) polymorphism on cognitive performance in suicide attempters with chronic schizophrenia. Methods: This polymorphism was detected in 114 suicide attempters and 617 non‐suicide attempters with chronic schizophrenia. Cognitive performance was assessed by the Repeatable Battery for the Assessment of Neuropsychological Status (RBANS). Results: The allelic and genotypic frequencies of this polymorphism between two groups did not differ after controlling for covariates (both, p > .05). There were no differences in RBANS scores between two groups after adjusting for covariates (all, p > .05). However, based on the genotype grouping in suicide attempters and non‐attempters, the attention score significantly differed after adjusting for covariates (both, p < .05). Further analysis indicated that this polymorphism was associated with attention score in suicide attempters ( p < .05), but not in non‐suicide attempters ( p > .05). Conclusions: DβH 5′‐Ins/Del polymorphism was not a risk locus of suicide attempters, but it was implicated in attention regulation in suicide attempters with chronic schizophrenia.